The new deep-sea families Cebocaridae fam. nov., Cyclocaridae fam. nov. and Thoriellidae fam. nov. (Crustacea: Amphipoda: Lysianassoidea) - Lowry, J. K.; Stoddart, H. E. (Zootaxa, 2011)
Within the Lysianassoidea three new families are established: Cebocaridae fam. nov. is established for the deep-sea bathypelagic genera Cebocaris J.L. Barnard, 1964; Crybelocephalus Tattersall, 1906; Crybelocyphocaris Shoemaker, 1945; Cyphocarioides Birstein & Vinogradov, 1970; Mesocyclocaris Birstein & Vinogradov, 1964; Mesocyphocaris Birstein & Vinogradov, 1960; Metacyclocaris Birstein & Vinogradov, 1955; Metacyphocaris Tattersall, 1906 and Paracyphocaris Chevreux, 1905; Cyclocaridae fam. nov. is established for the deep-sea demersal scavenging genus Cyclocaris Stebbing, 1888; and Thoriellidae fam. nov. is established for the abyssopelagic genera Chevreuxiella Stephensen, 1915, Danaella Stephensen, 1925, Parachevreuxiella Andres, 1987 and Thoriella Stephensen, 1915. The families Cebocaridae and Thoriellidae are reported from Australian waters for the first time, in the form of Metacyphocaris helgae Tattersall, 1906 and Parachevreuxiella justi sp. nov.